HIDROLISIS PROTEIN TINTA CUMI-CUMI (Loligo sp) DENGAN ENZIM PAPAIN - Kurniawan Kurniawan; Susi Lestari; Siti Hanggita R. J. (Universitas Sriwijaya, 2012)
The objective of this research were to know yield, protein content, free Î±-amino nitrogen, degree of hydrolysis, and amino acid of the result hydrolysis of ink protein squid (Loligo sp) with papain enzyme. The research used the method completely randomized design with two replications of the treatment factors, the difference in the concentration of the papain enzyme (0%, 1%, 2%, 3%, 4%, 5%, and 6%). The parameters of research were yield, protein content, free Î±-amino nitrogen, degree of hydrolysis, and amino acids. The results of research showed that differences in the concentration papain enzyme significant effect on the value of yield, protein content, free Î±-amino nitrogen, and degree of hydrolysis. Yield ranges from 78.05% to 88.61%, protein content from 28.90 mg/ml to 36.31 mg/ml, free Î±-amino nitrogen from 0.49 mg/ml to 10.99 mg/ml, the degree of hydrolysis from 0.016 to 0.345, and contains 14 kinds of amino acids of the 15 amino acids analyzed, histidine, arginine, threonine, valine, isoleucine, leucine, phenylalanine, lysine, glutamic acid, aspartic acid, serine, glycine, alanine, and tyrosine. The content of amino acid and degree of hydrolysis highest contained in the P2 treatment (papain enzyme concentration of 2%).